2012
DOI: 10.5483/bmbrep.2012.45.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring carbon catabolite repression for microbial cell factory

Abstract: Carbon catabolite repression (CCR) is a key regulatory system found in most microorganisms that ensures preferential utilization of energy-efficient carbon sources. CCR helps microorganisms obtain a proper balance between their metabolic capacity and the maximum sugar uptake capability. It also constrains the deregulated utilization of a preferred cognate substrate, enabling microorganisms to survive and dominate in natural environments. On the other side of the same coin lies the tenacious bottleneck in micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
61
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 100 publications
0
61
0
Order By: Relevance
“…Not surprisingly, numerous design strategies have been proposed to enable simultaneous sugar utilization in E. coli as well as other bacteria and yeast. Most of these efforts have focused on the coutilization of glucose and another sugar (36). Less effort has been directed toward the coutilization of nonglucose sugar (7,(37)(38)(39).…”
Section: Fig 6 (A)mentioning
confidence: 99%
“…Not surprisingly, numerous design strategies have been proposed to enable simultaneous sugar utilization in E. coli as well as other bacteria and yeast. Most of these efforts have focused on the coutilization of glucose and another sugar (36). Less effort has been directed toward the coutilization of nonglucose sugar (7,(37)(38)(39).…”
Section: Fig 6 (A)mentioning
confidence: 99%
“…Gu et al have shown that C. acetobutylicum ATCC 824 utilized 86% of glucose within 40 h, whereas only 6% of xylose was consumed even after an elongated incubation time (14). This sequential utilization extends fermentation time and results in incomplete substrate consumption (21,33). The phenomenon of preferring glucose over xylose is referred to as carbon catabolite repression, in which microorganisms preferentially utilize a rapidly metabolizable carbon source and inhibit the expression of some genes and enzyme activities related to the catabolism of nonpreferred carbon resources (21,33).…”
mentioning
confidence: 99%
“…This sequential utilization extends fermentation time and results in incomplete substrate consumption (21,33). The phenomenon of preferring glucose over xylose is referred to as carbon catabolite repression, in which microorganisms preferentially utilize a rapidly metabolizable carbon source and inhibit the expression of some genes and enzyme activities related to the catabolism of nonpreferred carbon resources (21,33). Unless glucose and xylose are both utilized efficiently, converting lignocellulosic biomass into biologically based products is unfavorable from an economic viewpoint (19,20,22), as yields would be limited.…”
mentioning
confidence: 99%
“…Originally known as the "glucose effect" [1], this mechanism enables some bacteria to preferentially catabolize certain energy substrates, e.g., Escherichia coli has preference for glucose even when lactose is readily available [2,3]. This "glucose effect" is often referred to as carbon catabolite repression (CCR) [4,5]. Depending upon the bacterial species, CCR involves one or a combination of mechanisms in gram-positive bacteria [2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…This "glucose effect" is often referred to as carbon catabolite repression (CCR) [4,5]. Depending upon the bacterial species, CCR involves one or a combination of mechanisms in gram-positive bacteria [2][3][4][5][6][7][8]. The repression can also be activated by catabolites other than glucose [2,8,9].…”
mentioning
confidence: 99%